EFFECT OF MAGNESIUM APPLICATION ON PHOSPHORUS USE EFFICIENCY (PUE) OF SOME PHOSPHATE FERTILIZERS AND ON MAGNESIUM AND PHOSPHORUS UPTAKE BY MAIZE (ZEA MAY L.) - & Jarallah, Al-Marsumy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
A field experiment was conducted to evaluate effect of magnesium application on efficiency of some phosphate fertilizers and phosphorus and magnesium uptake of maize. Three types of phosphate fertilizers (Triple super phosphate TSP, Di ammonium phosphate DAP and Urea phosphate UP) and five levels of magnesium (0, 25, 50, 75 and 100 kg Mg ha-1) as MgSO4.H2O were used in the study of. Randomized complete block design (RCBD) with three replicates were used. The results showed that the UP fertilizer was the most efficient in increasing P uptake, PUE and obtaining the highest response of maize compared with DAP and TSP. PUE, and they were 75.33, 64.23 and 56.96% for UP, DAP and TSP respectively. The results showed also that all of the plant parameters significantly increased as the level of Mg increased from 0 to 100 kg Mg ha-1. The level of 75 kg Mg ha-1 gave the highest values of P uptake in straw part, grains and total uptake and they were 97.87, 43.62 and 140.63 kg ha-1, while the level 100 kg Mg ha-1 gave the highest values for Mg uptake which were 71.57, 14.01 and 85.58 kg ha-1respectively. The results showed significant positive correlations of quadratic equation between magnesium level and all of studied parameters.